2019
DOI: 10.3390/nu11081838
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endoplasmic Reticulum and Oxidative Stress Parameters in the Pathophysiology of Disease-Related Malnutrition in Leukocytes of an Outpatient Population

Abstract: Cellular pathways such as inflammation or oxidative stress are the cause and triggers of disease-related malnutrition (DRM), but the influence of these markers on endoplasmic reticulum (ER) stress is unknown. The objective of this study was to analyze the relationship between mitochondrial function and ER stress parameters in a DRM population. The study population was composed of 82 outpatient subjects, of whom 45 were diagnosed with DRM and 37 were confirmed to be normonourished according to the American Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…Some studies have found increased inflammatory responses in patients with disease-related malnutrition [ 33 ], and our study observed a similar phenomenon. That is, both albumin and prealbumin showed a decreasing trend after surgery.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have found increased inflammatory responses in patients with disease-related malnutrition [ 33 ], and our study observed a similar phenomenon. That is, both albumin and prealbumin showed a decreasing trend after surgery.…”
Section: Discussionsupporting
confidence: 89%
“…It can promote the formation of reactive oxygen species (ROS), improve the oxidation level and reduce the function of the antioxidant defense system and induce the oxidative stress response in cells [24]. Moreover, ROS can also lead to endoplasmic reticulum stress and mitochondrial dysfunction through a series of pathways [25]. It has been reported that oxidative stress, mitochondrial dysfunction, and endoplasmic reticulum stress can eventually induce abnormal autophagy or excessive apoptosis, thus damaging cells and tissues and further affecting their biological activities [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…ER is formed from plasma membrane invaginations and is involved in several functions, including the biosynthesis of lipids and proteins and their storage, as well as regulating enzyme activity and metabolism [ 2 , 3 ]. Under conditions of cellular stress (e.g., malnutrition, overnutrition, and physical inactivity), ER induces an increase in the level of unfolded proteins [ 4 , 5 , 6 ]. The accumulation of unfolded proteins in ER lumen is responsible for triggering an unfolded protein response (UPR), which promotes morphophysiological changes capable of generating ER stress [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under conditions of cellular stress (e.g., malnutrition, overnutrition, and physical inactivity), ER induces an increase in the level of unfolded proteins [4][5][6]. The accumulation of unfolded proteins in ER lumen is responsible for triggering an unfolded protein response (UPR), which promotes morphophysiological changes capable of generating ER stress [7].…”
Section: Introductionmentioning
confidence: 99%